Elastic and inelastic scattering measurements for the 13C+208Pb system at close to the Coulomb barrier energies - Magro, P. L. D.; Guimarães, V.; Assunção, M.; Zevallos, E. O. N.; Angelo, M. B.; Garcia Figueroa, L. M.; Miletto, F.; Arazi, Andres; Hojman, Daniel Leonardo; Cardona, Maria Angelica; de Barbará, Ezequiel; Gomez, J.; et al. (Springer, 2024)
Fil: Magro, P. L. D.. Universidade de Sao Paulo; Brasil